Epidemiology of gastrointestinal parasites of small ruminants in Mymensingh, Bangladesh - Islam, Md. Shahidul; Hossain, Md. Shahadat; Dey, Anita Rani; Alim, Md. Abdul; Akter, Shirin; Alam, Mohammad Zahangir (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The current study was conducted to explore the prevalence of gastrointestinal (GI) parasites in small ruminants (sheep and goats) in relation to species, age, sex, season, and body condition in Mymensingh, Bangladesh. Materials and methods: A cross-sectional coprological survey was carried out at Mymensingh Sadar in Mymensingh from July 2015 to June 2016. In total, 433 fecal samples were screened for eggs/oocysts/cysts of parasite and counted by using standard qualitative and quantitative techniques. Eggs/oocysts/cysts were identified according to their characteristic features. Results: The study found 74.8% (n=324/433) prevalence of GI parasites in small ruminants. Species-wise prevalence indicated that 77.0% (n=268/348) goats and 65.9% (n=56/85) sheep harbored parasitic infection. Nine species of GI parasites were identified in the study area namely Strongyloides sp., Haemonchus sp., Oesophagostomum sp., Trichostrongylus sp., Trichuris sp., Paraphistomum spp., Fasciola spp., Eimeria spp. and Balantidium spp. The level of egg/oocyst/cyst per gram of feces (EPG/OPG/CPG) was ranged between 100 and 1200. Young small ruminants (78.4%) showed significantly (P=0.026) higher prevalence as compared to adult (68.8%). Between sexes, significantly (P=0.000) higher prevalence was found in female (83.6%) than male (64.7%). Infection was significantly (P=0.000) highest in poor body conditioned small ruminants (82.1%) as compared to moderate (72.2%) and good body conditioned (53.8%) small ruminants. In case of season, highest prevalence was found in rainy season (83.6%) followed by summer (78.6%) and winter (59.4%) with significant seasonal variations (P=0.000). Conclusion: Finally, GI parasites are endemic among small ruminants in the study area. Knowledge on these parasites and related epidemiological parameters is important for outlining fruitful control strategies against GI parasites. http://doi.org/10.5455/javar.2017.d234